SOURCES OF INFORMATION AMONG MEDICAL STUDENTS DURING THE COVID-19 PANDEMIC - Đokić, Milena; Djokic, Ana; Stanisavljevic, Tamara; Milic, Nikola; Milin Lazovic, Jelena (Medicinski podmladak, 2022)
Introduction: Relevant information about COVID-19 is crucial for disease prevention and its spread. The aim of this study was to assess sources of information among medical students during the COVID-19 pandemic. Material and methods: This cross-sectional study was conducted on 373 students of the Faculty of Medicine University of Belgrade. The anonymous questionnaire consisted of 3 parts: socio-demographic characteristics, information sources and the attitude towards available information about COVID-19. Questionnaire was available online during January 2021.Results: At the beginning of the pandemic, most students informed several times a day (37.5%), latter it would drop to beeing informed several times a week (33.8%) (p<0.05). Television and official websites were stated as the main information sources during the pandemic. Students of IV-VI year of medical school significantly more often informed themselves from official websites in contrast to I-III year students (75.5% vs 61.6%, p=0.014). More than 2/3 of the students stated that the information about the coronavirus is accurate and up-to-date, but only a third were satisfied with the information during the pandemic.Conclusion: The most common source of information among medical students during COVID-19 pandemic was television. The interest in being informed about the pandemic has decreased since its onset. Only a third of respondents were satisfied with the information availability during the pandemic.